Comparison of two pairs of primers used in polymerase chain reaction for the detection of human papillomaviruses in cervical smears - Magalhães, Ivna M. (2008)
Introduction: cervical cancer is the most frequent neoplasia among the women of countries in development. Great part of those cases is caused by persistent infection with different types of Human Papillomavirus (HPV) classified as high and low risk, according to the risk of cervical cancer deve lopment. Nowadays, it is believed that the best identification routine and follow up of the lesions in order to prevent the malignant transformation is the combination of the technique of Papanicolaou with the polymerase chain reaction (PCR), in which the amplification of conserved areas of the viral genome occurs, with use of degenerate primers, followed by type identification. The degenerate primers MY 09/11 are used worldwide, presen ting good sensibility and specificity. Recently, a new group of consensual primers denominated PGMY was described in the literature reformulating the primer MY and adding a new primer HMBO seeking to reduce losses of MY (false negative). Objective: compare two pairs of primers, MY and PGMY, to discorer the most appropriate for the diagnosis of infections caused by HPV in the uterine cervix for the technique of Polymerase chain reaction. Methods: a hundred and sixteen samples from cervical smears were evaluated. After DNA extraction, the PCR was done according to the protocols described in the literature. Results: we observed that the primers pair PGMY presents better sensibility and specificity in the detection of DNA of HPV when compared to the primers pair MY, it also presents better negative and positive predictive values. Conclusion: the new primers pair PGMY should be used to substitute the pair MY to improve the detection of the viral DNA.